Detection of the effect of climate change on the drainage of Aquifer of Birjand plain - Behzad Amraei (تحقیقات کاربردی علوم جغرافیایی)
Climate change is one of the most important challenges facing water resources management, including surface water and groundwater. The main purpose of this research is to detect the effect of droughts caused by the change in groundwater resources in Birjand plain. In this regard, using two nonparametric trend tests, the SENS and MAN-Kendal gradient estimates to detect the process of underground water level in Birjand city during the statistical period of 1370-1395 according to the statistics of the field of 47 areas of observation area (census water resources) Wentified. Using Pearson correlation matrix, correlation between climatic elements (Birjand station) temperature, precipitation and evapotranspiration and potential transpiration were calculated with the level of local city of Birjand, and based on a multivariate regression model for modeling the annual time series at the level of confidence level of 95 / 0 was developed. Climatic factors of 2080-2065 using the Output of the HADGEM2-ES model through the LARS-WG exponential model for the position of the Birjand station under two scenarios RCP8.5 and RCP2.6 were simulated and based on the regression model, the surface of the water Birjand city was simulated. The results indicated that firstly, in the base period (1370-1395), the surface of water in the area with an annual gradient of 47 centimeters per year was reduced. The correlation analysis indicated that three elements of rainfall, temperature and evapotranspiration were modeled in a linear composition of 75% of the annual changes in groundwater. The results of the microsterge model implemented on HADGEM2-ES data indicate that during the period 2035-2065 under both the scenario, groundwater level between 10 and 13 meters lower than the base period, which resulted from an increase in evapotranspiration And consequently, rainfall will be effective.